NEW ASPECTS OF TREATMENT OF COMPLICATIONS OF MENINGOENCEPHALITIS IN CHILDREN - Shukhrat Tashmirovich Niyozov; Ksenia Vladimirovna Shmyrina (Scholar Express Journals, 2022)
Favourably ended meningoencephalitis in childhood, can in the remote period manifest itself by neurological deficit in the form of mnemastic and sensory insufficiency. Transition from acute to chronic neuroinfection depends on the disturbances in the limbic area of the brain, and the timely use of etiotropic treatment obtained early will prevent severe complications. Such a drug is cerebralizine, and the improved method in the form of ozonation of cerebralizine will enhance its action and reduce the rehabilitation period(1,10)
Keywords: Children; Sequelae Of Meningoencephalitis; FIM Scale; Neuroimaging